Spending Review Integration Model in Budget Decision Making at the Ministry of Health of the Republic of Indonesia - Maryani, Dedeh; Asri, Jatnika Dwi; Ruslandi, Beni; meltarini, Meltarini (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The aim of this study is to identify an effective model for integrating spending reviews into the budget decision-making process. Using a qualitative approach, the study collects data through interviews and documentation. The findings suggest that the budget decision-making process would benefit from implementing an integration model known as the Comprehensive Monitoring and Evaluation Model of Budget Management. This model facilitates a more thorough review and oversight of budget allocations, ensuring better-informed decision making. The study recommends further research to assess the impact of this model on the quality of budget decision making, particularly focusing on how it enhances the decision-making process and improves budget management outcomes.